1982
DOI: 10.1007/bf02175894
|View full text |Cite
|
Sign up to set email alerts
|

Collagen types in keratoconus

Abstract: Collagen types in normal human and keratoconus corneas were separated by salt fractionation and thermal gelation in the pepsin-soluble fraction of the lyophilized tissues. Peptic digestion indicated no significant differences between normal and keratoconus corneas. Further collagen characterization was performed using SDS-PAGE. Collagen concentration were determined via hydroxyproline. Soluble collagens from normal human cornea represent 85% collagen type I, maximally 10% collagen type III and 5% collagen type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
0
8
1
Order By: Relevance
“…Radda et al have not shown expression changes in type V collagen in KC cornea 38 ; however, our sequencing and validation data shows upregulation of COL5A3 in the KC-affected cornea. These contradictory results could be due to the differences in corneal sample processing (collagen types were separated using salt fractionation and thermal gelation in the pepsin-soluble fraction of the lyophilized normal and KC human corneal tissues) 38 .…”
Section: Discussioncontrasting
confidence: 59%
“…Radda et al have not shown expression changes in type V collagen in KC cornea 38 ; however, our sequencing and validation data shows upregulation of COL5A3 in the KC-affected cornea. These contradictory results could be due to the differences in corneal sample processing (collagen types were separated using salt fractionation and thermal gelation in the pepsin-soluble fraction of the lyophilized normal and KC human corneal tissues) 38 .…”
Section: Discussioncontrasting
confidence: 59%
“…Radda et al (1982) found a 5 % increase in type I collagen in keratoconus, while Zimmermann et al (1988) found no differences in collagen composition of biochemical extracts from keratoconus. Analysis of expression of collagens by keratocytes in cell culture further clouds the issue: Newsome et al (1981) stated that collagen types I and III were synthesized in similar amounts by both normal and keratoconic derived stromal cells, while Peters et al, (1993) analysed four cultures of keratoconic cells and found that type I collagen and steady-state RNAs were reduced in cells from three of the four cultures.…”
Section: Extracellular Matrix Proteinsmentioning
confidence: 89%
“…The distribution of collagen types [1,2] as well as the posttranslational modification [2] of collagens were found to be within normal ranges. However, increased collagenolytic activities have been detected in keratoconus [3][4][5][6] and a suppressed translation of keratocyte RNA that could affect the synthesis of proteins like collagens has also been found [7,8].…”
Section: Introductionmentioning
confidence: 94%